(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the theory of parts of the sentence, focusing on their classification into primary, secondary, and tertiary components. It provides an overview of the principles underlying these categories, emphasizing their functional roles in sentence structure. Special attention is given to secondary parts, such as objects, attributes, and adverbial modifiers, which enhance the basic subject-predicate framework. The discussion also addresses the challenges associated with tertiary parts, including their definition, contextual variability, and overlap with pragmatics. The article concludes by highlighting the importance of this theory in understanding the complexity and adaptability of langu